prove that tan 13x-tan9x-tan4x=tan 9x tan13xtan 4x
Answers
Answered by
1
We have 13x = 9x + 4x
⇒ tan 13x = tan(9x + 4x)
We know that tan(A+B)=
⇒ tan 13x(1 – tan 9x tan 4x) = tan 9x + tan 4x
⇒ tan 13x – tan 13x tan 9x tan 4x = tan 9x + tan 4x
∴ tan 13x – tan 9x – tan 4x = tan 13x tan 9x tan 4x
Hence proved.
Answered by
0
We can write
13x=9x+4x
Tan14x=tan9x+4c
Tan13x=tan9x+tan4x/1-tan9x.tan4x
Tan13x-tan13x tan9x tan4x =tan9x+tan4x
Tan13x-tan4x-tan4x = tan13x tan9 tan 4x
Plz mark me in brain list
13x=9x+4x
Tan14x=tan9x+4c
Tan13x=tan9x+tan4x/1-tan9x.tan4x
Tan13x-tan13x tan9x tan4x =tan9x+tan4x
Tan13x-tan4x-tan4x = tan13x tan9 tan 4x
Plz mark me in brain list
Similar questions
Social Sciences,
1 month ago
Science,
1 month ago
Math,
3 months ago
Math,
11 months ago
Chemistry,
11 months ago